On the conversion of CO2 to value added products over composite PdZn and H-ZSM-5 catalysts: excess Zn over Pd, a compromise or a penalty?. Issue 13 (16th June 2020) - Ahoba-Sam, Christian; Borfecchia, Elisa; Lazzarini, Andrea; Bugaev, Aram; Isah, Abdulrahman Adamu; Taoufik, Mostafa; Bordiga, Silvia; Olsbye, Unni
Abstract : Zn was found to possess a dual role in composite PdZn–H-ZSM-5 catalysts for CO2 hydrogenation reactions: it promotes methanol formation when alloyed with Pd, but inhibits hydrocarbon formation by ion exchange with Brønsted acid sites in H-ZSM-5. Abstract : A challenge in converting CO2 into hydrocarbons (HC) via methanol (MeOH) is the gap between the optimal temperature for each step ( i.e. ≤250 °C for MeOH and ≥350 °C for HC). The focus of this study is to elucidate the cause of the limitations associated to oxygenate and hydrocarbon formation in combined PdZn and H-ZSM-5 catalysts at 250 to 350 °C. Starting with two different chemical states of Pd and Zn from two preparation approaches (physical mixture and surface organometallic chemistry grafting), operando X-ray absorption spectroscopy (XAS) and powder X-ray diffraction (PXRD) studies revealed similar PdZn alloy active phase formed during pretreatment in flowing H2 /Inert at 400 °C. The physical mixture performed better than the grafted analogue, with up to 8.8% yield to oxygenates (MeOH and dimethyl ether (DME); MeOH+) at 300 °C, close to the estimated thermodynamic yield (9.0%). The space–time yield (STY) of oxygenates increased from 250 to 300 °C, reaching 8.5 mol(MeOH+) kg(PdZn) −1 h −1 . The catalyst performance surpassed other reported yields in similar systems, which activity declined with temperature even below 300 °C. Operando XAS and PXRD experiments further showed that the PdZn phase active for MeOH formation was maintained during testing in the 250–350 °C range. InfraRed (FT-IR) and XAS experiments revealed the poisoning of Brønsted acid sites in H-ZSM-5 by Zn(ii ) exchange, thereby rendering it inactive for hydrocarbon formation. Overall, to avoid biasing the hybrid catalyst performance, a careful and balanced choice of the compositional characteristics will be crucial in designing an improved multi-functional catalytic system for CO2 valorisation.